Cribriform-morular variant of papillary thyroid carcinoma with poorly differentiated features: report of a case and review of the literature - Kusum L. Sharma; Ravi B. Singh; Nisreen Fidda; Ricardo V. Lloyd (BMC, 2022)
Abstract Introduction Cribrifrom-morular variant of papillary thyroid carcinoma (CMVPTC) is an uncommon thyroid neoplasm that occurs predominantly in women and is sometime associated with familial adenomatous polyposis (FAP). Some of these tumors may undergo dedifferentiation to poorly differentiated thyroid carcinoma (PDTC). We describe a rare case of this carcinoma in a women without a history of FAP. Case presentation A 49-year-old woman with a history of breast carcinoma presented with a thyroid mass. A CMVPTC was diagnosed after excision. There was no history of FAP. Histological examination showed classical features of CMVPTC in most areas, but about 20% of the carcinoma showed features of a poorly differentiated carcinoma with a solid pattern of growth, increase mitotic activity and a high Ki-67 proliferative index (25%). Immunohistochemical stains were positive for nuclear and cytoplasmic beta catenin staining. These special studies supported the diagnosis. Conclusion CMVPTC with dedifferentiation to PDTC is a rare carcinoma with only 4 previous documented cases in the literature. This aggressive variant of thyroid carcinoma is more common in females, as is CMVPTC, and is often associated with an aggressive biological course. The cases usually express nuclear beta catenin and estrogen, progesterone and androgen receptors have been reported in some cases. Some cases may have somatic alterations of the APC gene and TERT promoter mutations. These carcinomas may metastasize to lung, bones and lymph nodes. Because of its aggressive behavior, patient with this diagnosis should be treated aggressively to control disease spread and mortality from the carcinoma.